La Catedral de Vic a les darreries del segle XIV : edició i comentari de la visita pastoral de 1388 - Sureda i Jubany, Marc (Miscel·lània litúrgica catalana, 2010)
The record of the visit to Vic Cathedral in 1388 is the oldest preserved notice of a pastoral visit to this building. It constitutes a very interesting document for the evaluation of the reformation projects of bishop Pérez Calvillo in the circumstances of his pontificate, the development of the worship at Vic Cathedral in that moment, the operation of capitular administrations and offices and the material condition of the installations.